Removal of Foreign Body (Glass of Mirror) in Esophagus with Direct Laryngoscope - Fachzi Fitri; Deni Amri (Fakultas Kedokteran, Universitas Andalas, 2015)
AbstractLiterature contains fewer reports discussing the use of direct laryngoscope in esophageal foreign body extraction. Foreign bodies in esophagus was diagnosed based on anamnesis, physical examination, radiological finding. The choice of treatment influenced by many factors, such as the patient’s age and clinical condition, the size and shape of the ingested foreign body, the anatomic location and the skills of the physician. A case of impacted glass of mirror in esophagus and mental disorder in a 38 years old male was reported, which had been perfomed direct laryngoscope and an extraction with Magill forcep.Keywords: Foreign body, glass of mirror, direct laryngoscope, Magill forcepAbstrakSedikit sekali kepustakaan yang membahas mengenai penggunaan laringoskopi langsung pada pengangkatan benda asing esofagus. Benda asing esofagus didiagnosis berdasarkan anamnesis, pemeriksaan fisik, radiologi. Pilihan penatalaksanaan dipengaruhi oleh usia pasien dan kondisi klinis, ukuran dan bentuk benda asing, lokasi anatomi dan kemampuan dokter.Dilaporkan satu kasus kaca cermin di esofagus pada laki-laki usia 38 tahun dengan gangguan mental, yang telah dilakukan laringoskopi langsung dan ekstraksi dengan forsep Magill.Kata kunci: Benda asing, kaca cermin, laringoskopi langsung, Forsep Magill